Principal Academic Supervision in Improving Teacher Teaching Performance - Hosna, Rofiatul; ratna, endrik (SCHOOLAR: Social and Literature Study in Education, 2023)
This research examines the academic supervision of school principals in improving the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang. The research methodology used in this research is a qualitative method, which uses data collection techniques through interviews with school principals and teachers at MTs Madrasatul Qur'an Tebuireng Jombang. This research aims to find out how to improve the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang, what is the process of academic supervision of school principals in improving the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang, and what are the supporting and inhibiting factors for academic supervision principal in improving the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang. Academic supervision is a collaborative effort that has been defined as providing technical assistance to teachers and school staff in carrying out and facilitating the learning process. The aim is to improve the professional skills of teachers and staff, as well as to support students' academic progress. The principal is a supervisor in academic supervision. This research examines the academic supervision of school principals in improving the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang. The research methodology used in this research is a qualitative method, which uses data collection techniques through interviews with school principals and teachers at MTs Madrasatul Qur'an Tebuireng Jombang. This research aims to find out how to improve the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang, what is the process of academic supervision of school principals in improving the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang, and what are the supporting and inhibiting factors for academic supervision principal in improving the teaching performance of teachers at MTs Madrasatul Qur'an Tebuireng Jombang. Academic supervision is a collaborative effort that has been defined as providing technical assistance to teachers and school staff in carrying out and facilitating the learning process. The aim is to improve the professional skills of teachers and staff, as well as to support students' academic progress. The principal is a supervisor in academic supervision.